TGF-β1 inhibits human trophoblast cell invasion by upregulating cyclooxygenase-2. (August 2018) - Yi, Yuyin; Cheng, Jung-Chien; Klausen, Christian; Leung, Peter C.K.
Abstract: Introduction: Enhanced expression and activity of cyclooxygenase-2 (COX-2) has been reported in trophoblasts from women with preeclampsia compared with healthy pregnant women. Prostaglandin E2, the production of which is initiated by COX-2, and transforming growth factor-β1 (TGF-β1) have been shown to inhibit human trophoblast cell invasion. However, it is not known if TGF-β1 induces COX-2 in human trophoblast cells or whether COX-2 mediates the suppressive effects of TGF-β1 on trophoblast invasion. Methods: The effects of TGF-β1 on COX-2 expression were examined in the HTR-8/SVneo human trophoblast cells. The expression levels of mRNA and protein were examined by RT-qPCR and western blot, respectively. Pharmacological inhibitor and siRNA were applied to investigate the underlying molecular mechanisms. Cell invasiveness was examined by the Matrigel invasion assay. Results: Treatment with TGF-β1 induces both mRNA and protein levels of COX-2. Application of type I TGF-β receptor inhibitor SB431542 abolishes the stimulatory effects of TGF-β1 on COX-2 expression. Using an siRNA-mediated gene silencing approach, we demonstrate that activation of SMAD2/3 signaling is involved in the induction of COX-2 expression by TGF-β1. Furthermore, invasion assay shows that disruption of COX-2 expression or activity attenuates TGF-β1-inhibited cell invasion. Discussion: This study indicates that TGF-β1 upregulates COX-2 expression by activating SMAD2/3-SMAD4 signaling, and elevated COX-2 subsequently contributes to the suppression of human trophoblast cell invasion by TGF-β1. Clinically, targeting TGF-β1/COX-2 could be a useful therapeutic strategy for the treatment of placental disorders. Highlights: TGF-β1 induces COX-2 expression in human trophoblast cells. SMAD2 and SMAD3 are both involved in TGF-β1-induced COX-2 expression. COX-2 mediates TGF-β1-inhibited trophoblast cell invasion.